Accountability of Village Fund Management (Study on Gorua Village Government, North Tobelo Sub-district, North Halmahera Regency) - Iwan Duwila; Sofjan Alizar Sam (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The performance of the village government in managing the Village Fund, which is so large in amount, is expected to be utilized as much as possible in improving development and community welfare. However, the reality in the field does not match the expectations of the community. Some programs that have been proposed and agreed upon between the village government and the community are not implemented optimally. Therefore, the purpose of this study is to describe the accountability of the village government in managing village funds in Gorua Village, North Tobelo Sub-district. This research was conducted using qualitative research with a descriptive approach, where the author will explain social phenomena, from a number of field information related to the problem under study. Data collection techniques used were observation, interview and documentation. While the data analysis technique uses three stages, namely data reduction, data presentation, and conclusion. The results obtained from this study are (1) openness in presenting fund program information has not been fully implemented. This can be seen from several development programs that have not been completed but there is no information disclosure through budget and program accountability reports. (2) The lack of community participation in village development programs is due to the fact that the community has never been given information related to the progress of programs and budgets carried out.